MAPPING THE SCHOLARLY LANDSCAPE: REVISIT INTENTIONS AND MOTIVATION IN SOCIAL MEDIA INTERACTIONS - Jamalludin, Zulaffendi; Mohd Saman, Nur Rahmas; Abd Aziz, Noreen Noor (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2025)
This study comprehensive analysis of the scholarly landscape surrounding revisit intentions and motivation in social media interactions. With the ubiquitous use of social media platforms, understanding users’ revisit intentions and motivations is crucial. Despite growing interest, there remains a need to systematically map the research landscape, identify key contributors, and discern trends and gaps. Employing bibliometric analysis techniques, we examined publications from 2014 to 2023, utilizing scholarly databases and citation indices. Our methodology involved collecting and analysing publication data, including trends in output, author distribution, and subject areas. Visualizations and statistical analyses elucidated patterns and relationships. Our findings reveal a significant increase in publications, indicating a growing interest and maturity in the field. Fluctuations in publication rates were noted, potentially influenced by technological advancements, research priorities, and emerging trends. Dominant authors and collaborative networks were identified, offering insights into influential voices and collaboration opportunities. Additionally, the multidisciplinary nature of research on revisit intentions and social media interactions was highlighted. In conclusion, our study provides valuable insights into the scholarly landscape of revisit intentions and motivation in social media interactions. By mapping the research landscape and identifying key contributors, our findings can guide future research initiatives, foster collaborations, and inform decision-making processes. Moreover, our study contributes to a deeper understanding of users’ behaviours and interactions within the dynamic realm of social media.